Maternal fish oil and/or probiotics intervention: Allergic diseases in children up to two years old - Komulainen Miisa; Saros Lotta; Vahlberg Tero; Nermes Merja; Jartti Tuomas; Laitinen Kirsi (WILEY, 2025)
Background
As n-3 long-chain polyunsaturated fatty acids and probiotics possess immunomodulatory properties, theoretically they could lower the risk of allergic diseases. But their effects remain controversial. We aimed to study the effects of fish oil and probiotics separately or in combination from early pregnancy onwards to lower the risk of allergic diseases in the infants.
Methods
In this double-blind trial, women (n = 439) in early pregnancies were randomized into four intervention groups: fish oil + placebo, probiotics + placebo, fish oil + probiotics, and placebo + placebo. Fish oil (1.9 g docosahexaenoic acid and 0.22 g eicosapentaenoic acid) and probiotic (Lacticaseibacillus rhamnosus HN001 and Bifidobacterium animalis ssp. lactis 420, 1010 colony-forming units each) supplements were provided for daily consumption from randomization up to 6 months postpartum. All analyses were adjusted with pet ownership.
Results
No difference between the infants in the four intervention groups were found regarding physician-diagnosed food allergy, atopic eczema, or atopy at the age of 12 or 24 months (all p > .05). The probiotic intervention was associated with lower odds of recurrent wheezing at 24 months (OR 0.39, 95% CI 0.18-0.84, p = .017), but not at 12 months.
Conclusions
The use of fish oil and/or probiotics from early pregnancy onwards did not lower the odds of childhood allergic diseases or atopy, with the exception of the probiotic intervention which decreased the risk of recurrent wheezing when the infants were two years old. This suggests that the incidence of asthma could also decrease later in childhood and thus these outcomes need to be clarified in further investigations.